KARAKTERISTIK OPTIMUM BETON MUTU TINGGI DENGAN PENAMBAHAN SERBUK KACA - Ilham Nuruddin; Mochamad Teguh; Elvis Saputra (TEKNISIA, 2023)
Concrete material innovation is one of the most used in construction nowadays. Along with the infrastructure growth, the amount of waste increases, such as glass waste. The glass waste contains silica and can be used as filler in the concrete mixture. This study aimed to determine the influence of added glass powder as filler on high-strength concrete. This research method was a laboratory experiment testing high-strength concrete to seek optimum characteristics of high-strength concrete based on the glass powder composition added. The optimum concrete characteristics consist of compressive strength, tensile strength, and modulus of elasticity for five samples with different material compositions shown in Table 3, and each sample comprised 6 (six) specimens tested. This study found that the second sample achieved the optimum compressive strength of concrete with 47.07 MPa, more significant than the compressive strength design (fcr) of 45 MPa. The optimum tensile strength produced 3.91 MPa or 8.3%, which correlated to the compressive strength of the BSK2 sample. Similarly, the optimum modulus of elasticity was then computed based on laboratory compressive strength tests referring to SNI 2847:2019 and the ASTM C-469-94, resulting in 33271.7 MPa dan 36164.95 MPa, respectively. In contrast, the modulus elasticity calculated based on the weight volume of concrete referring to SNI 2847:2019 has reached the highest elasticity modulus on the first sample with 34384.8 MPa.